Indonesia’s Pulp Export Performance In the China Market: An Analysis Using Almost Ideal Demand System Approach - Natalia, Evi; Simangunsong, Bintang; Manurung, Elisa Ganda Togu (Agro Bali : Agricultural Journal, 2024)
Indonesia is one of the world's leading pulp producers. Both domestic consumption and global demand are increasing annually. As Indonesia seeks to meet the escalating global demand for pulp raw materials, China is emerging as a major destination for its exports, which underscores the strategic importance of this market. This study aims to evaluate the comparative advantage of Indonesian pulp exports and to identify the price, cross-price and expenditure elasticities of pulp demand in the Chinese market. Using the Revealed Comparative Advantage (RCA) method and the Linear Approximation-Almost Ideal Demand System (LA/AIDS) model, this research analyzes annual time series data covering the period 2003-2022, focusing on the quantity and export value of chemical pulp (HS 470329). The results show that Indonesian pulp has a comparative advantage in the Chinese market, as indicated by Indonesia's RCA index greater than one. However, this comparative advantage is declining over time. At the same time, China's sustained increase in pulp consumption underscores the intensified competition among pulp-exporting countries for market share in China. Using the LA/AIDS model, the estimation results highlight a different dynamic in the Chinese pulp market: Japanese pulp emerges as a complementary product to Indonesian pulp, while Thailand and Brazilian pulp act as substitutes. These findings have valuable strategic implications for Indonesian policymakers and industry stakeholders in managing the complexities of global pulp trade dynamics